The Sand Pebbles : a novel - McKenna, Richard, 1912-1964 (Harper & Row, 1962)
For years the U.S. Navy gunboat San Pablo has been patrolling a tributary of the Yangtze River in China protecting American missionaries and businessmen. Her crew has grown soft and lazy. Then the great Chinese Revolution of the 1920's breaks out. This is the story of the crew, particulary Jake Holman, as they face the precarious situation and make agonizing decisions.